2016
DOI: 10.5897/jphe2015.0765
|View full text |Cite
|
Sign up to set email alerts
|

Perception of obstetric danger signs among women living on the coastline of the Atlantic Ocean in rural Lagos, Nigeria

Abstract: Implementation of safe motherhood programs in sub-Saharan African nations requires recognition of signs of potential emergency obstetric cases to facilitate immediate care seeking and urgent medical intervention. This questionnaire-based survey aimed to describe the perception of obstetric danger signs among women of reproductive age, living on the Atlantic coastline of rural Lagos. This crosssectional, descriptive study took place in two non-congruent communities of Lagos State, Nigeria, between October 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
(19 reference statements)
2
5
4
Order By: Relevance
“…Women who visited a health facility for pregnancy less than four times were more than six times more likely to experience an ODS during pregnancy as compared to their counterparts. This is in good agreement with the standard WHO recommendation of antenatal care follow-ups and other findings [ 4 , 13 , 14 ]. This similarity may be mothers that visited ANC get adequate health information related to ODS during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Women who visited a health facility for pregnancy less than four times were more than six times more likely to experience an ODS during pregnancy as compared to their counterparts. This is in good agreement with the standard WHO recommendation of antenatal care follow-ups and other findings [ 4 , 13 , 14 ]. This similarity may be mothers that visited ANC get adequate health information related to ODS during pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…The study found 41.3% overall prevalence of ODS in the area. This finding was higher than the study conducted in Egypt and Nigeria [ 7 , 14 ] with 4.5% and 29.6%, respectively. This difference may be the use of different study areas; studies in Egypt and Nigeria were facility-based study, and still, not all maternal health service coverage was not 100%.…”
Section: Discussioncontrasting
confidence: 78%
“…In our study, 74.3% study subjects mentioned vaginal bleeding which is higher than study done in different part of Ethiopia Tsegedi district 49.1% [4] Debark town north west 66.8% [10] Adigrat 10.9% [14], Debra Birhan town 45.4% [16] Aleta Wondo, Southern 45.9% [18] Mekelle city Tigray 68.5% [24] Debaytilatgin district 53.7% [25] and other part of African countries like in Tanzania 50% [13] Mbarara district Uganda 49.2% [15] Burkina Faso 39.4% [26], Guatemala 31.0% [27], Rewa district of Madhya Pradesh [28], Southeast Nigeria 67% [21] Lagos, Nigeria 48.4% [29], Malawi 39% [30] Uganda 67.4% [31] Burkina Faso 24.8%, Ghana 29.3%, Tanzania 57.6% [32] Tanzania 19% [33] but lower than study done in Dar-es-salaam, Tanzania 81.2% [20] BRD Medical College, Gorakhpur, India 90.5% [34].…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports on obstetric risk perception and danger sign recognition in Nigeria [17182027]. Studies in other parts of Africa found that the proportion of women with knowledge of at least one obstetric danger sign ranged from 53% in Tanzania to 82.5% in Ethiopia [2428].…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, the corresponding figures among women were higher in Bangladesh (99.3%) than in Pakistan (64%) [32]. Studies in developing countries identified age at marriage, education, parity, extended family, place of residence, employment status, wealth, and previous hospital delivery as predictors of obstetric risk perception [2737]. Similarly, age, parity, education, knowledge and practice of antenatal care, previous institutional delivery, and experiencing maternal death in an acquaintance predicted awareness of obstetric danger signs [2736].…”
Section: Introductionmentioning
confidence: 99%